Citra Tubuh dan Presentasi Diri Online di Instagram: Dinamika Identitas Pada Dewasa Awal - Manullang, Patricia Desire Sabatina Lorenza; Sokang, Yasinta Astin (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of social media influencers on Instagram displaying ideal bodies has given rise to the concept of